PARIWISATA DAN KEMISKJNAN DI BALI - Suprastayasa, I Gusti Ngurah Agung (Pusat penelitian & Pengabdian Kepada Masyarakat STP Nusa Dua Bali, 2007)
The Tourism industry in Bali makes important contributions to the economies of Bali as well as Indonesia, particularly to foreign exchange earnings,  employment and GDP. However, the vast growth of tourism industry has not been able to eradicate poverty. Some measures should be made to make tourism generates more benefit to the poor. The private sector, community, Non-Government Organizations and governments should